Implementation of the KOTAKU Program in Alleviating Slums in the Eastern Region of Medan City - Siti Hazzah Nur Ritonga; Hairani Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The implementation of the City without Slum Program (KOTAKU) in Eradicating Slum in the Eastern Region of Medan City is a program run by the Directorate General of Human Settlements to support the fulfillment of the 2015-2019 RPJMN target. The KOTAKU program aims to develop urban areas through quality residential environments. The theory used in this study is the Van Metter and Van Horn theory which consists of Size and Policy Objectives, Resources, Characteristics of Implementing Agencies, Attitudes / Tendencies (Dispositions) of the Implementers, Inter-organizational Communication and Implementing Activities, and the Economic, Social, Environment and Politics. This study uses a descriptive method with a qualitative approach. The results showed that the implementation of the City without Slum Program (KOTAKU) in Alleviating Slum in the Eastern Region of Medan City is not yet in accordance with the needs of the local community so that it has not been realized properly and thoroughly. There are internal problems that have arisen so that the KOTAKU program that has been planned has not been realized. As for the inhibiting factors, namely the lack of socialization from the government regarding the program, and the lack of community participation in the development process. This research provides recommendations, namely, the government needs to increase socialization related to the program and monitor the implementation of the KOTAKU program and establish direct coordination with the community to increase community participation in the running of the KOTAKU program.